Conformational Analysis in Solution of a Chiral Bisoxazoline Molecule: Vibrational Circular Dichroism Spectroscopy and Density Functional Theory Study. (13th September 2011) - Aamouche, A.; Stephens, P. J.
Abstract : The conformations of the chiral bisoxazoline: 2, 2′-methylenebis[3a, 8a-dihydro-8H-indeno[1, 2-d]oxazole] (also named IndaBOX ), have been studied. Density functional theory (DFT) calculations identify four inequivalent stable conformations. Two, I and II have, C2 symmetry; two, III and IV, have C1 symmetry. The electronic energies of I–IV are ordered: I < II < III < IV . The span in energy is <1.0 kcal/mole. Vibrational unpolarised absorption and circular dichroism spectra have been predicted for the four conformations using DFT. Comparison of population-weighted spectra to experimental spectra of CHCl3 and CDCl3 solutions in mid-IR region strongly supports the DFT predictions of the number, structures, and relative energies of the conformations of IndaBOX . This shows that DFT predicts spectra with a high degree of reliability. We will undoubtedly illustrate the advantage added by vibrational circular dichroism spectroscopy in conformational analysis and in the absolute configuration determination.